Revision of Tarodes Pocock, 1899 and Udvardya Prószyński, 1992 (Araneae: Salticidae), with descriptions of two new species of Udvardya from New Guinea - Gardzińska, Joanna (Zootaxa, 2015)
Tarodes Pocock, 1899 and Udvardya Prószyński, 1992 are redefined and redescribed. The male of T. lineatus Pocock, 1899 and the female of U. elegans Prószyński, 1992 are redescribed for comparisons. Additionally, two species of Udvardya from New Guinea, U. bellatrix sp. nov. and U. fortis sp. nov., are diagnosed, described and illustrated. Geographical distribution of the species is given.